Teaching and learning strategy based on ihes and its relationship with teachers’ profession status in Selangor - Sapie Sabilan; Mohd Isa Hamzah; Ab. Halim Tamur; Zakiah Hassan (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study explains the ability of the Sekolah Rendah Agama (SRA) Jabatan Agama Islam Selangor (JAIS) teachers in selecting teaching strategies after following a series of teacher training programs related to the Integrated Holistic Education System (IHES). This study also explains the influence of the status of teachers in their ability to choose effective teaching strategies. In short, this study is a survey that uses the questionnaire method as a research instrument. The study sample was 535 SRA JAIS teachers out of a total population of 5,489 teachers covering nine districts in Selangor. Descriptive and inference analysis was performed using SPSS version 22.0 software. Through descriptive analysis of teachers' teaching strategies are at a high level and partly at a moderate level. About a one-way ANOVA test shows that there is a significant difference [F (2,532) = 4.081, p <0.05] between SRA JAIS teachers in terms of teacher teaching strategies and their job status. The implications of this study suggest that teacher training programs organized by JAIS on teaching and learning can be improved.